2017
DOI: 10.1111/tra.12461
|View full text |Cite
|
Sign up to set email alerts
|

The C‐terminal tails of heterotrimeric kinesin‐2 motor subunits directly bind to α‐tubulin1: Possible implications for cilia‐specific tubulin entry

Abstract: Funding informationTIFR, DAE, Government of India; DAE-SRC fellowship; UGC fellowship.The assembly of microtubule-based cytoskeleton propels the cilia and flagella growth. Previous studies have indicated that the kinesin-2 family motors transport tubulin into the cilia through intraflagellar transport. Here, we report a direct interaction between the C-terminal tail fragments of heterotrimeric kinesin-2 and α-tubulin1 isoforms in vitro. Blot overlay screen, affinity purification from tissue extracts, cosedimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 63 publications
2
13
0
Order By: Relevance
“…Taken together, our results argue that the C-terminal tail of KLP3B augments processivity, possibly by tethering the motor to the microtubule [52], which prevents premature dissociation. Attaching the motor at its C-terminus to beads in previous optical tweezers studies therefore likely curtailed the processivity of the kinesin-2 motor.…”
Section: Klp3a/b and Klp11/20 Motors Are Highly Processivesupporting
confidence: 53%
“…Taken together, our results argue that the C-terminal tail of KLP3B augments processivity, possibly by tethering the motor to the microtubule [52], which prevents premature dissociation. Attaching the motor at its C-terminus to beads in previous optical tweezers studies therefore likely curtailed the processivity of the kinesin-2 motor.…”
Section: Klp3a/b and Klp11/20 Motors Are Highly Processivesupporting
confidence: 53%
“…Recent studies have, however, stated that the motor subunits could independently interact with soluble proteins through the tail domain (Girotra et al, 2016; Sadananda et al, 2012). Here, we showed that the Kinesin-2α tail could also bind to a membrane-associated protein, Rab4.…”
Section: Discussionmentioning
confidence: 99%
“…For example, kinesin-2, which binds the α-tubulin C-terminus in vitro , has different binding affinities to tubulin isotype mixtures specific to different tissues. Overexpression of the kinesin-2 tail domain causes ciliogenesis defects [ 50 ], indicating that limiting motor protein affinity on the basis of tubulin isotype may function in regulating ciliary stability. Intriguingly, detailed correlative live cell imaging and EM in Chlamydomonas flagella demonstrated that anterograde IFT occupies B tubules, while retrograde IFT prefers A tubules of the same axoneme doublet; thus, a single doublet bears bidirectional cargo transport [ 51 ] ( Figure 2 ).…”
Section: Cilia and The Microtubule Cytoskeletonmentioning
confidence: 99%